Pengembangan Aplikasi Layanan Pasien Menerapkan Metode Rapid Aplication Development Berbasis Mobile - Putri Febriana Aulia; Muhammad Dedi Irawan (Journal of Information System Research (JOSH), 2023)
Smartphone technology is much loved by the public because there are many features that make it easier for public services, especially in the health sector. Obstacles that occur in clinics are the lack of transparency of registration information. conventional treatment, causing patient service treatment to be long. This research has the formulation of the problem of how to make a registration system that can be accessed by patients and can be carried out by the general public such as the community. The aim is to increase the quality and quality of polyclinic services and maximize the system more than before. In addition to building patient service applications as a digital health media with the Android platform using the React Native framework and the JavaScript programming language and MySQL database. So that it can make it easier for users to carry out registration, obtain accurate information, and be able to save more time without having to arrive early just to get a queue number in the Yazid Pratama clinic service. The officer experienced the same thing because the officer was able to provide the files before the patient arrived the previous day, so when the patient arrived the officer had already provided the necessary files, only requiring verification of the patient's data so he could continue for treatment. System development uses the RAD (Rapid Application Development) method and the acceptance result of this system is 88.5% using the User Acceptance Testing (UAT) method. It is hoped that this application will make it easier for patients to get effective, efficient, humane, fair health services without discrimination.